PENINGKATAN HASIL BELAJAR IPA SISWA SEKOLAH DASAR MENGGUNAKAN QUANTUM TEACHING - Haffit Mufarrid; Yalvema Miaz (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the low learning outcomes of elementary school science students. The purpose of this study was to determine the improvement of science learning outcomes of elementary school students by using quantum teaching. This research was a classroom action research conducted in class IV SDN 10 Pauh. These results indicated an increase in student learning outcomes starting from the initial ability of 65.13, cycle 1 got an average of 66.92 while cycle 2 got an average of 81.27. The results of this study indicated that there was an increase in the science learning outcomes of elementary school students by using quantum teaching. This study concluded that using quantum teaching can improve the learning outcomes of elementary school students. The implication of this research is that it can be used as a reference in improving science learning outcomes of elementary school students.